Survei Deteksi Dini Kelainan Refraksi Mata Menggunakan Snellen Chart Pada Siswa Kelas 5d SD Muhammadiyah 1 Surakarta - Widyatmoko, Yudha Pratama; Andini, Putri Dwi; Adzhani, Muhammad Pria; Kumala, Aswa Arsa; Febrian, Andre; Firda, Fatthiyatu Assa’diy (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Refractive disorders occur when the eye cannot focus light properly on the retina, resulting in blurred vision. Refractive disorders can be classified into myopia (eyes that are too long), hyperopia (eyes that are not long enough), and astigmatism (uneven focus due to the shape of the cornea). Correction through optical aids such as glasses, contact lenses, or refractive surgery is needed to obtain clear vision. Field observations carried out in class 5D of SD Muhammadiyah 1 Surakarta identified a concrete problem in the form of a high prevalence of refractive eye disorders. This condition is closely correlated with the low understanding of students and the school environment about the importance of maintaining visual health. This limited knowledge results in minimal preventive measures and early detection of refractive disorders. Based on these findings, interventions in the form of comprehensive education about eye health and implementation of early screening using the Snellen Chart are priority needs for the school community in Ketelan Village, Banjarsari District. This approach is expected to increase awareness and provide preventive solutions to the identified refractive disorder problems.